Musculoskeletal injuries in the young tennis player - Kibler, W. B.; Safran, M. R. (Clinics in Sports Medicine, 2000)
Tennis is becoming increasingly popular, especially with young athletes. Despite recent advances in epidemiologic research of tennis injuries, there still is a need for more injury research in all of the racquet sports. The data that does exist show that the young athlete is susceptible to injury in these different sports. Injury patterns in the skeletally immature racquet sports athlete are becoming apparent. Although most of the sports result in similar injury patterns, such as a predominance of lower extremity injury, there are differences. It appears that the physical demands of the sport are becoming more clearly documented, and the adaptive response to these demands is becoming understood. The adaptive response reveals a common origin for many of the injuries in the different sports. This is related most often to repetitive microtrauma with resultant loss in flexibility and strength. The sports medicine practitioner must understand these differences, know the demands, do serial musculoskeletal evaluations for maladaptations, and adhere to a periodized prehabilitation program of preventative exercises to maximize performance and minimize injury risk.